Analysis of Affecting Factor to Capital Structure Company - N Karniawaty; S F Setiawan; V S Nufus; A Asbin; Maulidina Aisyah (Peneliti.net, 2021)
The purpose of the research is to know the affecting factor of a capital structure company and to determine what factors can affect the company's capital structure. All companies certainly have a desire for their capital structure to run according to the goals set by the company. Therefore, companies need a capital structure to regulate all capital that goes in and out of the company. This research used a qualitative method with a descriptive approach. Moreover, data analysis was used to explain what is the capital structure, the choice of capital structure for the company, what factors can affect the capital structure, and what is the appropriate way for the company to run well. The results of this study show that a capital structure has a considerable influence on the company. This is happening because it can affect the smooth running of the company. A company that has high liquidity and profitability will not be subject to long-term debt but short-term debt, and if a company can hold its liquidity to keep running smoothly, a company will not easily fall and lose. Instead, the company will further develop because liquidity is well maintained.